Empowering women through targeting information or role models: Evidence from an experiment in agricultural extension in Uganda - Lecoutere, Els; Spielman, David J.; Van Campenhout, Bjorn (2021)
Prepared by Els Lecoutere, David J. Spielman, and Bjorn Van Campenhout